Poetry as enchantment and other essays - Gioia, Dana 1950- (Paul Dry Books, 2024)
"In the essays in Poetry as Enchantment-more personal than any of his earlier works-Dana Gioia shares a lifetime of thought and experience about poetry. Gioia, the author of Can Poetry Matter?, talks about poetry in a radically different way than it is currently being taught or discussed. In the title essay, he explains that poetry is speech raised to the level of song, and though poetry may often be misunderstood as intellectual, it moves us the way music does. Poetry charms its readers, creating a heightened experience of attention. It addresses readers in the fullness of their humanity, simultaneously speaking to the mind, emotions, imagination, memory, and physical sense. Without academic jargon, Poetry as Enchantment relates literature to the questions of life."--
Keywords: Poetry / Appreciation; Poetry / History and criticism; Poésie / Appréciation; Poésie / Histoire et critique; Literary criticism; Critiques littéraires